Synthesis and characterization of cDNA encoding a cartilage-specific short collagen. - Ninomiya, Y (1984)
Hyaline cartilage contains a unique set of collagenous proteins. Type II collagen is the most abundant, constituting about 85% of the total cartilage collagen. In addition, several minor collagenous components have been described. To study the structure and developmental regulation of chondrocyte-specific collagens, we have constructed a cDNA library from embryonic chicken sternal cartilage mRNA. We report here on the isolation and characterization of a 3200 base-pair-long cDNA that codes for a collagenous polypeptide of unusual structure in that the total length of the molecule is only about half of pro alpha 1(II) collagen chains. The mRNA for this polypeptide is considerably smaller than mRNA encoding the pro alpha chains of interstitial collagens. In addition, the peptide encoded by the cDNA appears to contain at least three domains with triple-helical potential separated by short, noncollagenous peptides. Between the three collagenous domains are several cysteinyl residues.